Advances in hospitality and leisure. Volume 3 / Joseph S Chen - Chen, Joseph S.
Advances in Hospitality and Leisure, a peer-review serial published annually, delivers refreshing insights of a host of scientific studies pertaining to hospitality, leisure, and tourism while providing a forum to stimulate discussions on contemporary issues and emerging trends essential to theory advancement as well as professional practices from a global perspective. The main focus of this serial is to divulge the innovative methods of inquiry so as to inspire new research topics that are vital and have been in large neglected. The serial attempts to address the needs of the populace willing.